THE TEACHING READING COMPREHENSION OF HORTATORY EXPOSITION TEXT TO THE ELEVENTH GRADE STUDENTS IN MEDAN - Nova Marya Simanjuntak; Berlin Sibarani; Johannes Jefria Gultom (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
The objectives of this study were to describe how the teachers teach reading comprehension of hortatory exposition text to the eleventh grade students in Medan and to reveal the underlying reasons why they did that way. This study was conducted by using descriptive qualitative design. The subjects of this study were two English teachers who taught at the eleventh grade students at SMA Methodist 8 Medan in academic year 2016/2017. The data were collected by observing, video recording and interviewing and analyzed by using Miles and Huberman technique (1994). The findings of the study showed that most of the teachers’ way are not yet focusing on teaching reading comprehension but rather focusing to the teaching the knowledge of the genre. The underlying reasons of the teachers’ ways in teaching reading comprehension did not facilitate reading comprehension. It was due to the misperception of the concept of teaching reading comprehension. Keywords: teaching, reading comprehension, hortatory exposition text